2008
DOI: 10.1542/peds.2007-0808
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Hypoglycemia by Children With Type 1 Diabetes 6 to 11 Years of Age and Their Parents: A Field Study

Abstract: Ability to recognize hypoglycemia is a significant problem for children with type 1 diabetes and their parents. For children, poor ability to detect low blood glucose levels may be a significant and underappreciated risk factor for severe hypoglycemia. More effort is needed to provide education and training designed to improve hypoglycemia detection in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 16 publications
0
41
2
1
Order By: Relevance
“…372 Depressive symptoms may be associated with poorer blood glucose monitoring 373,374 and poorer diabetes mellitus control. 361,[375][376][377] Depressive symptoms are also associated with impaired hypoglycemia awareness 378 and may independently predict proteinuria. 379 A study of 276 adolescents with diabetes mellitus found that blood glucose monitoring frequency explains 38% of the association between HbA 1c and depressive symptoms (ie, with depressive symptoms, blood glucose monitoring decreases and HbA 1c increases).…”
Section: Depressionmentioning
confidence: 99%
“…372 Depressive symptoms may be associated with poorer blood glucose monitoring 373,374 and poorer diabetes mellitus control. 361,[375][376][377] Depressive symptoms are also associated with impaired hypoglycemia awareness 378 and may independently predict proteinuria. 379 A study of 276 adolescents with diabetes mellitus found that blood glucose monitoring frequency explains 38% of the association between HbA 1c and depressive symptoms (ie, with depressive symptoms, blood glucose monitoring decreases and HbA 1c increases).…”
Section: Depressionmentioning
confidence: 99%
“…In addition, although it is commonly recognized that patients with longstanding diabetes, those with autonomic neuropathy, and those in the geriatric population frequently cannot recognize serious hypoglycemia, children and their parents also do poorly in recognizing hypoglycemia. In a recent study 22 of children ages 6-11 years and their parents, both parents and children frequently did not recognize hypoglycemia. The parents failed to note low glucose levels of < 54 mg/dl in their children > 50% of the time, and the …”
Section: Case Studymentioning
confidence: 94%
“…22 The deception may be carried out, as in this case, by patients writing down false values instead of the reported results from their glucose meter, 23 or by fabricating results not performed at all, or in more subtle ways such as avoiding performing SMBG at times when they know their glucose levels are either too high or too low.…”
Section: Case Studymentioning
confidence: 99%
“…Severe hypoglycemia may lead to physical and psychosocial morbidities such as brain damage, loss of consciousness, depression and low self-esteem [1]. It is also well known as death-in-bed syndrome [2].…”
Section: Introductionmentioning
confidence: 99%